HVAC CFD Analysis of Air Flow and Temperature Distribution Inside Passenger Compartment - Darlis, Nofrizalidris; Ishak, Izuan Amin; Sulaiman, Syabillah; Jaat, Norrizam; Hakim, Abdul Fathul (Journal of Automotive Powertrain and Transportation Technology, 2021)
The thermal environment and air quality in a passenger car can affect driver's and passengers' health, performance and comfort. Due to spatial and temporal variation of state variables and boundary conditions in the vehicle cabin, the heating, ventilating and air-conditioning (HVAC) does not have to be designed to provide a uniform environment. This are due to individual differences regarding to physiological and psychological response, clothing insulation, activity, air temperature and air movement preference. Experimental study in vehicle HVAC system can be very costly to be conducted. In order to analyze the air flow and temperature distribution in passengers compartment, a numerical simulation was used in this study to analyze the air flow and temperature distribution of HVAC unit inside Proton Exora passengers compartment, with the air blower speed and air temperature used as parameter, to evaluate the airflow behavior and temperature distribution in the compartment. The simulation data obtained is then compared to the experimental data, showing good agreement between these two methods.